Pengaruh Konsentrasi Gelatin dan Karagenan Terhadap Karakteristik Fisik, Kimia dan Organoleptik Pada Velva Jambu Biji - Septiandhani, Anugraheni; Herawati, Maria Marina (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This research aims to determie the effects of gelatin and carrageenan concentrations on the quality of red guava velva based on physical, chemical, and organoleptic properties, and to find the best concentration of gelatin or carrageenan on the quality in red guava velva based on physical, chemical, and organoleptic properties. This research used a non-factorial Randomized Block Design (RBD) technique by varying the concentration of gelatin and carrageenan used in guava velva. Data analysis of test results was tested using analysis of variance ANOVA (Analysis of Variance) test with a significance level of 5%, if it was significant then a further test was carried out using the Duncan Multiple Range Test (DMRT). The research results showed that (1) the best treatment for physical characteristics was Carrageenan 0.75% which had the highest overrun value of 15.5%; total dissolved solids 19.5 brix; melting power 21.61 minutes and viscosity 3698.25cP; (2) The best treatment for chemical characteristics is 0.50% Gelatin treatment, namely 186.30; (3) The best organoleptic test results were that 0.75% Carrageenan produced a soft and smooth texture that was liked by the panelists.